Comparison of laryngoscopic, glottal and vibratory parameters among Estill qualities – Case study - Frič, Marek; Dobrovolná, Alena; Andrade, Pedro Amarante (2023)
Estill Voice Training (EVT) is an effective educational system for developing and controlling distinct voice qualities used in contemporary commercial singing. EVT teaches six vocal qualities that differ at 13 levels. This study aims to investigate whether the distinct vocal qualities taught by EVT can be systematically differentiated based on laryngoscopic observations and vocal fold oscillation parameters. To investigate the differences in six EVT qualities, laryngeal dimensions and glottal area waveform parameters were measured in a single female subject who performed it in one-octave scale. Glottis Analysis Tools (GAT) were used to measure these parameters and phonovibrograms were obtained from the analysis. The resulting data were subjected to factor analysis to identify the systematic differences between EVT qualities. High-speed videolaryngoscopy analysis revealed a significant influence of vocal qualities on vocal fold oscillations. The factor analysis of the data identified three factors based on laryngeal dimension and four factors derived from GAT parameters. The first GAT factor was influenced by posterior adduction and distinguished belt quality from other qualities, suggesting a significant influence of the aryepiglottic sphincter. The second GAT factor contained parameters derived from glottal length and amplitude, suggesting a relationship not only with vocal registers but also with laryngeal height. The third GAT factor was best related to body-cover figure and phonation type (membranous medialization), while the fourth GAT factor was related to the amplitude-length-ratio. These findings suggest that vocal fold oscillations can be used to distinguish between Estill voice qualities.